Influence of orthodontic brackets design and surface properties on the cariogenic Streptococcus mutans adhesion - Raphaella Barcellos Fernandes; Ana Bárbara Polo; Vinicius Novaes Rocha; Robert Willer Farinazzo Vitral; Ana Carolina Morais Apolônio; Marcio José da Silva Campos (Elsevier, 2022)
Objective: To compare the surface properties of self-ligating metallic (SLM), ceramic esthetic, and conventional metallic (CM) brackets, and evaluate the adhesion of Streptococcus mutans biofilms to their surface, attempting to interpret the correlation between bracket type and enamel demineralization from a microbiological perspective. Materials and methods: Twenty-two brackets of each group were used. The brackets' surface roughness was defined and the bacterial adhesion was performed using the strain S. mutans ATCC25175 with 8 h or 24 h of incubation time. The total bacterial adhesion (TBA) of biofilms was assessed using optical density (OD) methodology. To quantify bacteria viability (BV), the colony forming units (CFU) were counted. A scanning electron microscopy (SEM) observation of biofilms was also performed. Results: Ceramic brackets exhibited significantly higher roughness (0.304) compared to CM (0.090) and SLM (0.067) ones (C > CM = SLM). The data obtained with the TBA and BV tests showed that S. mutans biofilm formed on bracket groups exhibited similar results for both incubation periods. From the SEM images it is possible to observe that biofilm structure formed for 24 h was denser than that for 8 h of incubation with significantly more aggregates and cells for three groups. Conclusion: This in vitro study suggests that despite the higher surface roughness of ceramic brackets, this alone does not influence the adhesion of the S. mutans biofilms. Clinical relevance: From a microbiological perspective, the bracket's design may be more relevant than its surface roughness with respect to the adhesion of cariogenic bacteria biofilm with potential risk to dental enamel integrity.